How the Traditional Industrial Manufacturer Miele Established a New Smart Home Division. Issue 4 (3rd July 2020) - Kaiser, Ingo; Stummer, Christian
Overview: Smart connected products are transforming existing markets and creating new ones. The smart homes market is one popular example. This transformation is particularly challenging for large, traditional industrial manufacturers that often rely on organizational structures that have evolved over decades. To adapt, some companies collaborate with or acquire startups, establish subsidiary firms, or encourage spinoffs in an effort to leave the "old firm" untouched while simultaneously seizing an opportunity to participate in the new market. Other companies are more adventurous and transform their organizational structure. Miele, the leading manufacturer of premium domestic appliances, is among the latter. We describe how Miele met this challenge in 2016 and discuss lessons learned in the four years after the company initiated its transformation process.